Morphological properties of moat-drift systems around the world - Henriette Wilckens; Tilmann Schwenk; Thomas Lüdmann; Christian Betzler; Wenyan Zhang; Jiayue Chen; Francisco Javier Hernandéz-Molina; Alice Lefebvre; Antonio Cattaneo; Volkhard Spieß; Elda Miramontes (PANGAEA, 2023)
To facilitate a comprehensive study of moat-drift systems, we analysed moats from different locations around the world. We measured the following morphological parameters: width, relief, slope angle, drift angle. As there is no moat without an associated drift, we see them as one system that we refer to as a moat-drift system. The moat trough is the deepest point in the moat and the drift crest the shallowest point of the contourite drift. The moat width is defined as the horizontal distance between the drift crest and the slope. The relief is defined as the vertical distance between moat trough and drift crest. The slope angle and the drift angle are the average gradient in both flanks of the moat: 1) between the moat trough and the slope and 2) between the moat trough and the drift crest. The previously published moats were measured from the seismic or sub-bottom profiler cross sections that were published either in a journal or on the GeoMapApp (www.geomapapp.org). In the cases in where multibeam data are available, we measured the parameters from the bathymetric map.